Cement pressurizing reduces radiolucent lines at glenoid: A randomized, multicentric study. (February 2021) - Kasten, Philip; Raiss, Patric; Zeifang, Felix; Stangl, Richard; Greiner, Stefan; Zumstein, Matthias; Nowotny, Jörg; Schmitt, Katrin; Schnetzke, Marc; Reuther, Falk; Frauenschuh, Dirk
Background: The hypothesis of this study is that cement pressurization into the glenoid reduces the rate of radiolucent lines in total shoulder arthroplasty in the mean 25.5 months after the operation. Methods: To examine this effect, a multicentric prospective randomized study (level of evidence 1) was initiated: one group (group P, n = 24) received intraoperative pressurization of cement into the cancellous bone of the glenoid, the other cement without pressure (group NoP, n = 27). Inclusion criteria were an osteoarthritis with glenoid erosion <15° and an intact rotator cuff. Results: There were no significant differences preoperatively between the groups regarding age (mean age 66 ± 10 years (range 44–81)), gender, range of motion, scores and pathomorphology. Both groups had a significant improvement of the scores, strength, motion and satisfaction 25.5 months after the intervention. The scores were similar between the groups (ns). However, cement pressurization at the glenoid side significantly reduced the incidence of radiolucent lines (p < 0.027). Conclusion: This supports the use of this simple technique to improve long-term survival of total shoulder arthroplasty. Level of evidence: 1